2009
DOI: 10.4319/lo.2010.55.1.0354
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of turbulence in fish shoals

Abstract: Turbulence was measured in situ within shoals of juvenile perch Perca fluviatilis with a self-contained autonomous microstructure profiler near an artificial reef in Lake Constance, Germany. Depth-averaged dissipation rates of turbulent kinetic energy (TKE) correlated with the density of shoaling fish, providing evidence for fish-induced turbulence in a large and stratified lake. The observed range and the depth-averaged values of TKE dissipation rates associated with fish-generated turbulence were comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 46 publications
2
26
2
Order By: Relevance
“…Using in situ observation data, Gregg & Horne (2009) reported that mixing inside fish schools was 100 times less efficient for vertical mixing of density-stratified water than that due to physically induced turbulence, consistent with Visser (2007). In contrast, based on field campaigns with turbulence measurements, net samplings, still image recordings and acoustic surveys, Lorke & Probst (2010) found that, regardless of whether turbulence was measured inside or outside of fish schools, roughly 20% of the turbulent kinetic energy was used for vertical mixing of density. Katija & Dabiri (2009) pointed out that fluid viscosity and body shapes, rather than generated eddy size, are important in determining the efficiency of swimming-induced mixing, as the viscous fluids can be drifted along the swimming organisms, and that more efficient swimmers are more efficient in drifting fluid around their bodies: the length of drifted water along the streamline, not the body length, is the important scale.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Using in situ observation data, Gregg & Horne (2009) reported that mixing inside fish schools was 100 times less efficient for vertical mixing of density-stratified water than that due to physically induced turbulence, consistent with Visser (2007). In contrast, based on field campaigns with turbulence measurements, net samplings, still image recordings and acoustic surveys, Lorke & Probst (2010) found that, regardless of whether turbulence was measured inside or outside of fish schools, roughly 20% of the turbulent kinetic energy was used for vertical mixing of density. Katija & Dabiri (2009) pointed out that fluid viscosity and body shapes, rather than generated eddy size, are important in determining the efficiency of swimming-induced mixing, as the viscous fluids can be drifted along the swimming organisms, and that more efficient swimmers are more efficient in drifting fluid around their bodies: the length of drifted water along the streamline, not the body length, is the important scale.…”
Section: Introductionmentioning
confidence: 59%
“…Kunze et al (2006) , with high acoustic backscatter intensity that was likely anchovy schools in Monterey Bay, USA. Lorke & Probst (2010) reported ε = 3 × 10 -9 to 1 × 10 -8 W kg −1 based on fast response temperature sensor data in freshwater fish schools in Lake Constance, Germany. All the above studies used microstructure profilers similar to this study for measuring turbulence.…”
Section: Dissipation Ratesmentioning
confidence: 99%
“…Dissipation rates in aggregations were found to be 10-100 times the maximum dissipation rates outside aggregations; however, the mixing efficiency decreased 100-fold within the aggregation, resulting in essentially the same eddy diffusivity (K  ) inside and outside the school of fish (Gregg and Horne, 2009). Although these findings demonstrate that mixing within aggregations of fish is less efficient than mixing produced by background turbulence, a separate study of fish shoals moving horizontally in shallower water found that mixing efficiency did not differ between profiles with or without fish (Lorke and Probst, 2010). The conflicting conclusions from these studies illustrate the variability and challenges faced when characterizing biogenic mixing.…”
Section: Mixing Via Biogenic Turbulencementioning
confidence: 84%
“…The occurrences of intense biogenic turbulence were often infrequent and difficult to predict in prior sampling studies (Kunze et al, 2006;Gregg and Horne, 2009;Lorke and Probst, 2010). A program to collect data over a 3year period in Saanich Inlet and at an open ocean field site was later conducted to generate statistics on biogenic mixing (Rousseau et al, 2010).…”
Section: Mixing Via Biogenic Turbulencementioning
confidence: 99%
See 1 more Smart Citation